Analysis on Displacement Angle of Phase-Shifted Carrier PWM for Modular Multilevel Converter - Qian Cheng; Chenchen Wang; Jian Wang (Energies, 2020)
This paper provides theoretical and experimental discussions on the characteristics of the modular multilevel converter (MMC) when phase-shifted carrier sinusoidal pulse-width modulation (PSC-SPWM) is applied. Harmonic-cancellation characteristics of output voltage and circulating current are analyzed on the basis of a general implementation of PSC-SPWM with two freedom displacement angles. Five available PSC-SPWM schemes with different carrier displacement angles were obtained, and a detailed performance comparison about output voltage and circulating current harmonic characteristics is presented. On the basis of the equivalent circuit with ideal transformer representation of the SMs, capacitor voltages affected by PSC-SPWM schemes are also briefly analyzed. The proposed PSC-SPWM schemes can unify two different cases of odd and even SM situations for output voltage and circulating current harmonic minimization, respectively. Lastly, the optimal schemes for practical MMC application were verified by simulation and experiments on an MMC prototype.